Recognising efforts by a woman farmer - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
This set features Mwanaisha Said Mbogolo, an 85 year old widow, who lives with her seven grandchildren in Mbuzii village, Lushoto in the Northern part of the Tanga region. Mwanaisha relies on agriculture to feed her large family. She experiences many problems as the head of the family since she is old and frail. Previously, she found it hard to feed her family as she kept one cow and grew crops on her farm with little produce. However following support from the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), International Centre for Tropical Agriculture (CIAT) and a number of partners, Mwanaisha has adopted improved farming practices such as use of improved seed varieties, fertilizers and timely land preparation. Recently, she used 10 kgs of improved bean variety (Selian 90) on a quarter acre of her farm and harvested 80 Kg.